Azo dye polyelectrolyte multilayer films reversibly re-soluble with visible light - Kim, Mikhail; Hillel, Coral; Edwards, Kayrel; Borchers, Tristan H.; Mermut, Ozzy; Pietro, William J.; Barrett, Christopher J. (Frontiers in Materials, 2024)
Polymeric multilayer films were prepared using a layer-by-layer (LBL) technique on glass surfaces, by repeated and sequential dipping into dilute aqueous solutions of various combinations of water-soluble polyanions (polyacrylic acid (PAA)), polycations (polyallylamine hydrochloride (PAH) or chitosan (CS)), with bi-functional water-soluble cationic azo dyes bismark brown R (BBR) or bismark brown Y (BBY), or anionic azo dyes allura red (ALR) or amaranth (AMA), as ionic cross-linkers. The electrostatically-assembled ionically-paired films showed good long-term stability to dissolution, with no re-solubility in water. However, upon exposure to low power visible light under running water, the films photo-disassembled back to their water-soluble constituent components, via structural photo-isomerization of the azo ionic crosslinkers. The relative rate of the disassembly (RRD) of the films was established using UV-Vis spectroscopy, demonstrating that these assemblies can in principle represent fully recyclable, environmentally structurally degradable materials triggered by exposure to sunlight, with full recovery of starting components. A density functional theory treatment of the allura red azo dye rationalizes the geometrical isomerization mechanism of the photo-disassembly and provides insight into the energetics of the optically-induced structural changes that trigger the disassembly and recovery.